Evaluasi Karakteristik Sifat Fisik Tanah Berdasarkan Variasi Lereng dan Hubungannya dengan Produksi Tanaman Kelapa Sawit (Elaeis guineensis Jacq) di Kecamatan Wawotobi Kabupaten Konawe - Gilang, Gilang; Rembon, Fransiscus S.; Yusuf, Dewi Nurhayati; Pasolon, Yulius B; Alam, Syamsu; Rustam, La Ode (Agritechpedia, 2024)
Soil physical characteristics refer to the depth of soil drainage and soil structure and influence root development and water availability, the drainage of which influences oil palm plant production. This research aims to analyze the condition of soil physical properties on different slopes and their relationship with oil palm production located at PT. Tani Prima Makmur, with coordinates 3°00′ – 4°25′ South Latitude and 121°73′ – 123°15. Namely Afdeling of Lawulo, Anggotoa, and Wawotobi. Analysis includes soil texture, water content, organic matter, total pores, permeability and slope class. Using the survey method, Soil samples were taken in three sections with 3 slope classes, namely sloping (0-15%), slightly steep (15-25%) and steep (25-45%). Soil samples were taken to the Soil Science Laboratory. The research results show ed that Soil in the three subdivisions the a variety of textures from sandy loam to clay, water content tends to be high (16,92%-25,75%). The organic matter content (2.15%-5.09%), while the bulk density is high (1.35-1.86 g cm-3), indicates a fairly significant level of soil density. Soil permeability varies from moderate to very slow (1.96-2.75 cm h-1), especially in Afdeling Lawulo. Total pore space (30%-49%). Production data on lower slopes has a higher FFB weight than steeper slopes. Proper soil management is needed to increase oil palm productivity, especially in maintaining a balance between water retention and good drainage in each planting area